'Mama take us to a country where there is no war': COVID-19 and mental health challenges for Syrian refugee women in Lebanon. Issue 1 (2nd January 2021) - Karajerjian, Sarine
ABSTRACT: This paper is an account of my research with Syrian women living in Beirut, Lebanon. I follow the trajectory of Syrian women and the fear and anxiety that has accompanied it, which undermine their mental health. Such a trajectory started with the trauma of the war. It was followed by being forced to leave their homes and possessions to move to Beirut, Lebanon. In Lebanon, these women faced a myriad of challenges, ranging from lack of employment and changes in gender roles and family dynamics, to experiences of discrimination as Syrian refugees from a bureaucratic system that treated them unfairly, and which undermined their hopes of finding opportunities for a better and safer future for their children. These all contribute to their current mental health status, yet again under attack from both the Beirut explosion of 4 August 2020, and by the wide-reaching impacts of COVID-19.